Implementation of a Participatory Approach to Improve Access to and Motivation for Primary Education for Children in Boralan Hamlet - Rusmiyati; Nugroho, Febri Ardi; Fatimah; Hikmah, Gina Nur; Rizqiy, Raliya; Utaminingsih, Rizka; A’yun, Nadzifatul; Zulkarnain, Abi Hasna; Az Zahra, Fiza; Maulana, Muhamad Arbhi; Maulidi, M Nizar; Zuraifa; Kamal, Muhammad Badrul; Anggraeni, Wulan Eka Septi; Guspul, Ahmad (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study aims to improve children’s learning participation and motivation in Boralan Hamlet by addressing low school engagement caused by parents’ limited understanding of education, not poverty. Through a participatory program, it involves families, schools, and the community to support dropouts and increase access to education. Method: This study used a mixed-method approach, combining surveys and interviews with observations, document reviews, and community focus group discussions. The program had four steps: identifying education barriers, training parents and local facilitators, running learning activities through the Community Learning Center (PKBM), and providing ongoing mentoring and evaluation. Quantitative data were analyzed using descriptive statistics, while qualitative data were grouped into themes to understand community experiences and opinions. Practical Applications: The findings offer practical guidance for improving education in rural areas by involving families and communities to boost motivation and help dropouts return to learning. Strengthening PKBM centers and using community-driven approaches can support inclusive, non-formal education initiatives. Conclusion: The participatory education program in Boralan Hamlet successfully increased children’s motivation and learning participation. The structured, multi-stakeholder approach—focusing on empowering families and strengthening PKBM—proved to be a sustainable and replicable model for improving access to basic education in underserved communities.